Polypropylene composite material with high thermal conductivity and good appearance and preparation method thereof

By using photodeposition technology to load Ag nanoparticles in polypropylene, the problem of insufficient thermal conductivity of polypropylene is solved, and a polypropylene composite material with high thermal conductivity and good appearance is achieved, which is suitable for thermal management and electronic packaging fields.

CN119912747APending Publication Date: 2025-05-02GUANGDONG ALDEX NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909132.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Polypropylene has poor thermal conductivity, which limits its application in areas where efficient thermal management is required, especially in electronic products, battery modules, electronic component heat dissipation, and automotive engine compartment.

Method used

By adopting photodeposition technology, Ag nanoparticles are loaded on the surface of sheet hexagonal boron nitride to form sheet hexagonal boron nitride supported by Ag nanoparticles, and mixed them with polypropylene, inorganic filler, compatible agent, antioxidant and dispersant to prepare a polypropylene composite material with high thermal conductivity and good appearance.

Benefits of technology

It significantly improves the thermal conductivity of polypropylene materials, improves the mechanical properties and appearance of the materials, extends the service life, and improves the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205170980000021
    Figure BDA0005205170980000021
  • Figure BDA0005205170980000041
    Figure BDA0005205170980000041
  • Figure BDA0005205170980000131
    Figure BDA0005205170980000131
Patent Text Reader

Abstract

The invention discloses a polypropylene composite material with high thermal conductivity and good appearance and a preparation method thereof, and belongs to the technical field of high polymer materials. The polypropylene composite material with high thermal conductivity and good appearance is prepared from the following components in parts by mass: 70 to 88 parts of polypropylene, 5 to 20 parts of Ag nanoparticle loaded flaky hexagonal boron nitride, 5 to 20 parts of inorganic filler, 2 to 4 parts of compatilizer, 0.3 part of antioxidant and 0.3 part of dispersing agent, ag nanoparticles are loaded on flaky hexagonal boron nitride and are added into polypropylene, so that the heat conductivity of the composite material is remarkably improved, heat dissipation can be effectively accelerated, and rapid cooling is realized; in addition, due to the synergistic effect of the Ag nanoparticles and the hexagonal boron nitride, the heat conduction efficiency of the polypropylene is remarkably improved, and the addition amount of the hexagonal boron nitride is effectively reduced, so that good appearance and excellent mechanical strength of the composite material are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polypropylene composite material with high thermal conductivity and good appearance and a preparation method thereof. Background Art

[0002] Polypropylene (PP) is a common thermoplastic. It is widely used in packaging, automobiles, home appliances, medical equipment and other industries due to its strong chemical stability, low density, easy processing and low cost. However, the poor thermal conductivity of polypropylene limits its application in fields that require efficient thermal management, especially in electronic products, battery modules, electronic component heat dissipation and automobile engine compartments. Materials with excellent thermal conductivity are required to ensure the efficiency and stability of the thermal management system. The thermal conductivity of polypropylene is usually only 0.1 to 0.2 W / (m·K), which makes it difficult to meet the requirements in environments with high thermal requirements. Therefore, how to improve the thermal conductivity of polypropylene while maintaining its other excellent properties has become a key issue in material improvement.

[0003] Hexagonal boron nitride (h-BN) is a white layered crystal with a structure similar to graphite, so it is also called "white graphite". Due to its high thermal conductivity, good electrical insulation properties, excellent chemical stability, low dielectric constant and low dielectric loss, h-BN has become one of the commonly used fillers for thermal conductive materials. Compared with traditional materials such as alumina, h-BN has higher volume resistivity and better thermal conductivity, and its unique lamellar structure allows the size and thickness of the lamellar to be controlled. After orientation treatment, h-BN can form more thermal conductive channels, which helps to reduce the resistance of heat conduction. In addition, h-BN also has the advantages of high temperature resistance, oxidation resistance and excellent chemical stability. However, in practical applications, there are still some challenges and shortcomings, which are mainly manifested in the following aspects: In order to significantly improve the thermal conductivity of composite materials, a higher proportion of boron nitride fillers are usually required, but too much filler will lead to a decrease in the mechanical properties of the material, especially the tensile strength and impact resistance are significantly weakened, thereby affecting the overall mechanical stability of the material. In addition, a high filler ratio may also cause uneven dispersion of boron nitride in the polymer matrix, forming agglomeration or local aggregation, which not only increases interface defects but also leads to poor appearance. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a polypropylene composite material with high thermal conductivity and good appearance and a preparation method thereof, thereby solving the problems in the prior art.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A polypropylene composite material comprises the following raw materials in parts by weight:

[0007]

[0008] The preparation process of the Ag nanoparticle-loaded flaky hexagonal boron nitride is as follows:

[0009] Add boron nitride flakes into triethanolamine aqueous solution and add AgNO3 at the same time; then seal the container, introduce argon gas to expel the air in the container, use a xenon lamp as a light source, and irradiate with a cutoff filter; after the reaction is completed, centrifuge and dry to obtain the product.

[0010] The mass fraction of AgNO3 relative to hexagonal boron nitride is 0.5-3wt%.

[0011] The volume fraction of the triethanolamine is 10-30%; the thickness of the flake hexagonal boron nitride is 1-3 μm; and the size of the Ag nanoparticles is 50-200 nm.

[0012] The polypropylene is at least one of homopolymer polypropylene and block copolymer polypropylene.

[0013] The inorganic filler is one or more of calcium carbonate, talc, mica and silica lime.

[0014] The compatibilizer is maleic anhydride-polypropylene graft.

[0015] The antioxidant is at least one of hindered phenols, thioesters, and phosphites;

[0016] The dispersant is at least one of calcium stearate and N,N-ethylenebisstearamide.

[0017] The method for preparing the above-mentioned polypropylene composite material comprises the following steps:

[0018] Weigh polypropylene, Ag nanoparticle-loaded hexagonal boron nitride flakes, inorganic filler, compatibilizer, antioxidant, and dispersant according to the above mass fractions and add them into a high-speed mixer for high-speed mixing to obtain a mixture;

[0019] The mixed material is put into a screw extruder for melting, extruding and granulating to obtain the product.

[0020] The above-mentioned polypropylene composite material is used in the preparation of electronic component housings.

[0021] Beneficial effects of the present invention:

[0022] 1. The present invention innovatively adopts photodeposition technology to successfully load metal Ag nanoparticles on the surface of flaky hexagonal boron nitride. This method can achieve uniform dispersion of silver nanoparticles. These nanoscale silver particles not only have excellent thermal conductivity, but also produce a synergistic effect with hexagonal boron nitride materials. The loading of silver particles effectively improves the thermal conductivity of hexagonal boron nitride. At the same time, the synergistic effect of the two significantly enhances the overall thermal conductivity of polypropylene materials. This technology provides a new way to improve the thermal conductivity of polymer materials such as polypropylene, and has broad application prospects, especially in the fields of thermal management, electronic packaging and composite materials. It can effectively improve the thermal conductivity of materials, extend their service life and improve overall performance.

[0023] 2. The present invention reduces the amount of hexagonal boron nitride added by introducing Ag nanoparticles into the flake hexagonal boron nitride. Excessive fillers will lead to a decrease in the mechanical properties of the material, especially the tensile strength and impact resistance will be significantly weakened, thereby affecting the overall mechanical stability of the material. The reduction in the amount of hexagonal boron nitride added can effectively improve the appearance and mechanical properties of the prepared polypropylene resin.

[0024] 3. The present invention discloses a polypropylene composite material with excellent thermal conductivity and good appearance. Compared with the traditional physical blending method of nano-Ag powder and flaky hexagonal boron nitride, the present invention makes the combination between Ag nanoparticles and hexagonal boron nitride tighter by optically depositing Ag nanoparticles on the surface of hexagonal boron nitride. This method can not only effectively enhance the interaction between the two, but also significantly improve the thermal conductivity of the composite material. Through the optical deposition technology, Ag nanoparticles can be evenly distributed on the surface of hexagonal boron nitride to form a stable interface structure, thereby promoting the formation of a thermal conductivity path and achieving a significant improvement in the thermal conductivity effect. Compared with the physical mixing method, the thermal conductivity of the composite material is more excellent. In addition, the introduction of Ag nanoparticles can also improve the appearance of the material, avoid the uneven dispersion or agglomeration of fillers that may occur in traditional methods, and further improve the surface quality of the polypropylene composite material. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] A polypropylene composite material with high thermal conductivity and good appearance, comprising the following raw materials in parts by weight:

[0027]

[0028] The polypropylene is at least one of homopolymer polypropylene and block copolymer polypropylene.

[0029] The inorganic filler is one or more of calcium carbonate, talc, mica and silicate lime, and its average particle size is 0.5-10 μm.

[0030] The compatibilizer is maleic anhydride-polypropylene graft.

[0031] The antioxidant is at least one of hindered phenols, thioesters, and phosphites; preferably, the hindered phenol antioxidant is antioxidant 1076, the thioester antioxidant is DSTP, and the phosphite antioxidant is antioxidant 168;

[0032] The dispersant is at least one of calcium stearate and N,N-ethylenebisstearamide.

[0033] The preparation process of Ag nanoparticle-supported hexagonal boron nitride is as follows:

[0034] Add boron nitride flakes into triethanolamine aqueous solution, and add 0.5-3wt% AgNO3 relative to the mass fraction of boron nitride; then seal the container, pass argon gas to exhaust the air in the container, use a xenon lamp as the light source, and equip it with a 420nm cutoff filter, irradiate for 4-12h, after irradiation, Ag + It can be reduced to Ag single substance and loaded on boron nitride; after the reaction is completed, the Ag nanoparticle-loaded boron nitride flakes are obtained after centrifugal drying;

[0035] The volume fraction of triethanolamine is 10-30%; the thickness of the flake hexagonal boron nitride is 1-3 μm; and the size of the Ag nanoparticles is 50-200 nm.

[0036] The method for preparing a polypropylene composite material with high thermal conductivity and good appearance comprises the following steps:

[0037] Step 1, weighing polypropylene, Ag nanoparticle-loaded hexagonal boron nitride flakes, inorganic filler, compatibilizer, antioxidant, and dispersant according to the above mass fractions and adding them into a high-speed mixer for high-speed mixing to obtain a mixture;

[0038] Step 2: putting the mixed material into a screw extruder for melting, extruding and granulating to obtain a polypropylene composite material with high thermal conductivity and good appearance.

[0039] The screw extruder is a parallel twin-screw extruder, and the temperatures of each section of the extruder are: 170-175°C for the first section, 180-190°C for the second section, 200-205°C for the third section, 205-210°C for the fourth section, 200-205°C for the fifth section, and the die head temperature is 205-210°C. The screw speed is 350-500r / min, and the vacuum degree is maintained in the range of -0.04 to -0.08MPa.

[0040] The technical scheme of the present invention is described below by the following examples and comparative examples;

[0041] Wherein, all raw materials and equipment in the embodiments and comparative examples are as follows:

[0042] Polypropylene: density 0.9g / cm 3 , shrinkage is 1.80%, heat deformation temperature is 94℃ under 0.45MPa pressure, melt index is 25.4g / 10min, impact strength is 3.6kJ / m 2 , produced by Wuhan Petrochemical Company;

[0043] Hexagonal boron nitride: purity is 98%, produced by Chaotai Metal Materials Co., Ltd.

[0044] Triethanolamine: purity 97%, produced by Aladdin Reagent Company;

[0045] Calcium carbonate: produced by Jiangxi Guangyuan Chemical Co., Ltd.;

[0046] Talc: produced by Liaoning Aihai Talc Co., Ltd.

[0047] Mica: produced by Jiangmen Jingda Mica Materials Co., Ltd.

[0048] Silica lime: produced by Jinan Huimianchuan Chemical Co., Ltd.;

[0049] Polypropylene grafted with maleic anhydride: produced by Coase Chemical Co., Ltd.;

[0050] AgNO3: purity is AR grade, produced by Aladdin Reagent Company;

[0051] Deionized water: produced by RO reverse osmosis method;

[0052] The twin-screw extruder used is AK-36 twin-screw extruder, produced by Nanjing Keya Chemical Equipment Co., Ltd.

[0053] Example 1

[0054] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0055] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 0.5wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 4h, after the reaction is completed, centrifuging and drying in an oven at 80℃ for 24h to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0056] S2, by mass, weigh 70 parts of polypropylene, 6 parts of Ag nanoparticle-loaded flake hexagonal boron nitride, 20 parts of calcium carbonate, 4 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0057] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the die temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0058] Example 2

[0059] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0060] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 1wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 6h, after the reaction is completed, centrifuging and drying in an 80℃ oven for 24h to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0061] S2, by mass, weigh 75 parts of polypropylene, 10 parts of Ag nanoparticle-loaded flaky hexagonal boron nitride, 12 parts of talc, 3 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0062] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set as follows: 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the die head temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0063] Example 3

[0064] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0065] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 1.5wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 8h, after the reaction is completed, centrifuging and drying in an oven at 80℃ for 24h to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0066] S2, accurately weigh 80 parts of polypropylene, 12 parts of Ag nanoparticle-loaded flake hexagonal boron nitride, 6 parts of mica, 2 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, by mass, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0067] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the die temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0068] Example 4

[0069] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0070] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 2wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 10 hours, after the reaction is completed, centrifuging and drying in an oven at 80℃ for 24 hours to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0071] S2, accurately weigh 78 parts of polypropylene, 15 parts of Ag nanoparticle-loaded flaky hexagonal boron nitride, 5 parts of wollastonite, 2 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, by mass, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0072] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the die temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0073] Example 5

[0074] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0075] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 2.5wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 12h, after the reaction is completed, centrifuging and drying in an 80℃ oven for 24h to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0076] S2, accurately weigh 88 parts of polypropylene, 5 parts of Ag nanoparticle-loaded flake hexagonal boron nitride, 5 parts of calcium carbonate, 2 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, by mass, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0077] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the die temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0078] Example 6

[0079] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0080] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 3wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 6h, after the reaction is completed, centrifuging and drying in an oven at 80℃ for 24h to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0081] S2, accurately weigh 70 parts of polypropylene, 20 parts of Ag nanoparticle-loaded flaky hexagonal boron nitride, 6 parts of talc, 4 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, by mass, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0082] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the die temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0083] Example 7

[0084] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0085] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 1wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 4h, after the reaction is completed, centrifuging and drying in an oven at 80℃ for 24h to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0086] S2, accurately weigh 75 parts of polypropylene, 15 parts of Ag nanoparticle-loaded flake hexagonal boron nitride, 7 parts of calcium carbonate, 3 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, by mass, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0087] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the die temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0088] Example 8

[0089] This embodiment provides a polypropylene composite material with high thermal conductivity and good appearance, and a preparation method thereof comprises the following steps:

[0090] S1, adding flaky boron nitride to a 10% volume fraction of triethanolamine aqueous solution, and adding 1wt% AgNO3 relative to the mass fraction of boron nitride, placing it in a 1000mL single-necked flask and ultrasonicating it for 30 minutes, then sealing the container, passing argon gas to exhaust the air in the container, using a xenon lamp as a light source, and equipped with a 420nm cutoff filter, the irradiation time is 4h, after the reaction is completed, centrifuging and drying in an oven at 80℃ for 24h to obtain flaky hexagonal boron nitride loaded with Ag nanoparticles.

[0091] S2, accurately weigh 75 parts of polypropylene, 15 parts of Ag nanoparticle-loaded flake hexagonal boron nitride, 7 parts of calcium carbonate, 3 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, by mass, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0092] S3, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the barrel temperature of the parallel twin-screw extruder is set at 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the head temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0093] Comparative Example 1

[0094] This embodiment provides a polypropylene composite material, and the preparation method thereof comprises the following steps:

[0095] S1, accurately weigh 85 parts of polypropylene, 12 parts of talc, 3 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, by mass, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0096] S2, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the head temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0097] Comparative Example 2

[0098] S1, by mass, weigh 93 parts of polypropylene, 5 parts of wollastonite, 2 parts of polypropylene grafted maleic anhydride, 0.1 parts of antioxidant 1076, 0.2 parts of antioxidant 168, and 0.3 parts of dispersant EBS, add them into a high-speed mixer and mix at high speed for 6 minutes to obtain a mixture.

[0099] S2, the mixed material is put into a parallel twin-screw extruder for melting treatment, and then subjected to extrusion, granulation and drying processes. In this process, the temperature of each section of the parallel twin-screw extruder is set to 170°C for the first section, 185°C for the second section, 200°C for the third section, 210°C for the fourth section, 205°C for the fifth section, the head temperature is 210°C, the screw speed is 450r / min, and the vacuum degree is maintained at -0.06MPa, and finally a polypropylene composite material with high thermal conductivity and good appearance is obtained.

[0100] Experimental testing

[0101] The raw material components of the embodiments and comparative examples are shown in Table 1 below:

[0102] Table 1 Raw material components of the embodiments and comparative examples (parts by mass)

[0103]

[0104]

[0105] According to relevant testing standards, the physical properties of the products in the above embodiments and comparative examples were tested, including tensile strength (MPa), flexural modulus (MPa), cantilever beam notched impact strength (kJ / m 2 ,23℃), thermal conductivity (W / (m·k)), and the physical property test results are shown in Table 2.

[0106] Table 2 Physical property test results of the products of the embodiments and comparative examples

[0107]

[0108]

[0109] From the test results in Table 2, it can be obtained that as the content of Ag nanoparticle-loaded hexagonal boron nitride (Ag@h-BN) increases, the thermal conductivity of the polypropylene composite material gradually increases. When the addition amount of Ag@h-BN reaches 15%, the thermal conductivity reaches a maximum value of 3.3W / (m·k). However, when the content of Ag@h-BN reaches 20%, the thermal conductivity of the polypropylene composite material no longer increases, probably because the excess Ag@h-BN limits the transfer of heat. Compared with Comparative Example 1, after adding 10% of Ag@h-BN in Example 2, the thermal conductivity of the composite material is significantly improved, indicating that the prepared Ag@h-BN has good thermal conductivity. At the same time, compared with Comparative Example 1, the mechanical properties of Example 2 are not significantly reduced. Examples 3-5 further increase the content of Ag@h-BN, and the thermal conductivity is further increased, and the thermal conductivity can reach a maximum of 3.3W / (m·k), which confirms the excellent thermal conductivity under the synergistic effect of Ag@h-BN.

[0110] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0111] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A polypropylene composite material, characterized in that: The invention comprises the following raw materials in parts by weight:

2. A polypropylene composite material according to claim 1, characterized in that: The preparation process of the Ag nanoparticle-loaded flaky hexagonal boron nitride is as follows: Add boron nitride flakes into triethanolamine aqueous solution and add AgNO3 at the same time; then seal the container, introduce argon gas to expel the air in the container, use a xenon lamp as a light source, and irradiate with a cutoff filter; after the reaction is completed, centrifuge and dry to obtain the product.

3. A polypropylene composite material according to claim 2, characterized in that: The mass fraction of AgNO3 relative to hexagonal boron nitride is 0.5-3wt%.

4. A polypropylene composite material according to claim 2, characterized in that: The volume fraction of the triethanolamine is 10-30%; the thickness of the flake hexagonal boron nitride is 1-3 μm; and the size of the Ag nanoparticles is 50-200 nm.

5. A polypropylene composite material according to claim 1, characterized in that: The polypropylene is at least one of homopolymer polypropylene and block copolymer polypropylene.

6. A polypropylene composite material according to claim 1, characterized in that: The inorganic filler is one or more of calcium carbonate, talc, mica and silica lime.

7. A polypropylene composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride-polypropylene graft.

8. The polypropylene composite material according to claim 1, characterized in that: The antioxidant is at least one of hindered phenols, thioesters, and phosphites; The dispersant is at least one of calcium stearate and N,N-ethylenebisstearamide.

9. The method for preparing a polypropylene composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh polypropylene, Ag nanoparticle-loaded hexagonal boron nitride flakes, inorganic filler, compatibilizer, antioxidant, and dispersant according to the above mass fractions and add them into a high-speed mixer for high-speed mixing to obtain a mixture; The mixed material is put into a screw extruder for melting, extruding and granulating to obtain the product.

10. Use of a polypropylene composite material according to any one of claims 1 to 8 in preparing electronic component housings.